Evaluation of safflower varieties for productivity and quality in the arid conditions of the Northern Caspian region - N. A. Zaitseva; I. I. Klimova (Аграрная наука Евро-Северо-Востока, 2023)
In a dry continental climate, safflower has an undeniable advantage over grains and oilseeds due to its morphological structure. The main advantage of this crop is that it is capable of extracting water from deep layers of soil with its developed root system, and due to the structural features of the vegetative mass, it can use it economically, while forming stable yields. Therefore, the search for promising varieties for the selection of new varieties, especially in the arid conditions of the Astrakhan region, continues to be relevant. Over the course of three years (2019-2021), there were studied 28 collection varieties of safflower of various ecological and geographical origin from the Federal Research Center N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR). During the study period, 12 varieties were identified from the collection under study based on the yield and a number of economically valuable traits for further use in breeding work. The productivity of the selected samples of the studied collection varied greatly, depending on the conditions of the year and on average exceeded the standard variety Astrakhansky 747 by 0.08...0.23 t/ha. At the same time, the highest yield of the selected samples was from Tajikistan (619 Tsam-buli, 618 Shahalli-260) and Kazakhstan (620 Shirkas, 622 Center 70) – 0.43...0.51 t/ha, that was 0.15…0.23 t/ha higher than the standard. According to the oil content in the seeds (0.5...1.9 % higher than the standard) the following varieties were identified: 621 Talan (Kazakhstan) – 30.3 %, 584 Sinaloa-90 (Mexico) – 30.3 %, 619 Tsambuli (Tajikistan) – 29.4 %, 609 Akmai (Kazakhstan) – 29.1 %. The development of new varieties based on selected samples will allow to obtain stable yields in extremely arid conditions of the region.